The Impact Of Digital Marketing And Marketing Mix On The Sales Level Of Inc Food - Indah Dwi Pravitasari; Nabila Akmas; Yuniva Sari (Universitas Kristen Indonesia Toraja, 2023)
. Along with the era and market changes, digital marketing is a means for economic actors for their marketing needs. People's behavior has changed drastically; of course, the cause is due to advances in technology. The development of information technology via the internet, an instrument that changes the way people obtain information. The marketing mix in the digital marketing process will design integrated marketing programs that are able to provide superior value for buyers. The marketing mix means product, price, place and promotion. For service products, the 4P can be added to the 3P, those are people, process and physical evidence. Inc food is a business that uses digital marketing and a marketing mix that operates in the culinary.